2011
DOI: 10.1002/jcb.23267
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid inhibits macrophage SOCS3 expression and enhances cytokine production

Abstract: Suppressor of cytokine signaling-3 (SOCS3) has multiple functions including inhibition of Janus kinase activity, regulation of protein degradation, and suppression of cytokine signaling. SOCS3 modulates macrophage response to cytokines such as IL-6 and leptin that are systemically induced in obesity. Obesity is a suspected risk factor for SOCS3-related pathology such as rheumatoid arthritis and Crohn’s disease as well as zoledronic acid (ZA)-induced osteonecrosis of the jaw (ONJ). Thus, understanding the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 37 publications
(48 reference statements)
0
46
0
Order By: Relevance
“…Recent studies have demonstrated that suppressor of cytokine signaling-3 (SOCS3) can repress the proinflammatory M1 macrophage phenotype, whereas SOCS3 deficiency promotes M1 macrophage polarization and inflammation via an increased production of proinflammatory cytokines IL-1β, IL-6, IL-12 and IL23, rendering a microenvironment conditioned for the differentiation of Th1 and Th17 cells (49, 50). Interestingly, zoledronic acid has been shown to induce M2-like tumor associated macrophages (TAMs) toward an M1 phenotype (51) and enhances proinflammatory cytokine production through inhibition of SOCS3 expression in macrophages (19). These findings could explain the mechanisms whereby zoledronic acid drives Th17 differentiation, at least in part, through promoting M1-macrophage polarization and activation (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated that suppressor of cytokine signaling-3 (SOCS3) can repress the proinflammatory M1 macrophage phenotype, whereas SOCS3 deficiency promotes M1 macrophage polarization and inflammation via an increased production of proinflammatory cytokines IL-1β, IL-6, IL-12 and IL23, rendering a microenvironment conditioned for the differentiation of Th1 and Th17 cells (49, 50). Interestingly, zoledronic acid has been shown to induce M2-like tumor associated macrophages (TAMs) toward an M1 phenotype (51) and enhances proinflammatory cytokine production through inhibition of SOCS3 expression in macrophages (19). These findings could explain the mechanisms whereby zoledronic acid drives Th17 differentiation, at least in part, through promoting M1-macrophage polarization and activation (18).…”
Section: Discussionmentioning
confidence: 99%
“…The tumor associated macrophages (TAMs) with similar characteristics of M2 macrophages can suppress immune response and promote angiogenesis and metastasis of tumor cells, thus facilitating cancer progression, or attenuating inflammation and enhancing wound healing (54). Recently, both in vitro and in vivo studies have shown that tumor macrophages are potential targets of BPs (18, 19, 51), possibly via the manipulation of macrophage phenotypes in tumor microenvironment, and by similar mechanisms, sustain prolonged inflammation leading to an increased susceptibility to BRONJ. Epidemiologic study has identified several risk factors associated with ONJ; in cancer patients receiving high-dose intravenous BPs for the prevention and treatment of skeletal-related complications, treatment with other anti-tumor drugs including glucocorticoid (dexamethasone), chemotherapeutic or/and anti-angiogenic drugs incur additional risks; as such, it should be further explored whether BPs and these anti-tumor drugs have any cooperative effects on the immune system, specifically on the interplay between Th17 cells and M1/M2 macrophages, as these immune cells potentially function as a “double-edge” sword within the tumor microenvironment to enhance both anti-tumor immunity and inflammatory responses (18, 39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, monocytes treated with ZA and IL-2 displayed an increased phosphorylation of p38 compared to monocytes treated with either IL-2 or ZA alone (data not shown). Moreover, SOCS3 inhibition by ZA [23,24] resulting in enhanced STAT1/3 signaling may contribute to increased IFN-γ production when IL-2 was added to cultures.It is well known that isopentenyl pyrophosphate (IPP) accumulates in monocytes when treated with ZA [25]. Monocytes that accumulate IPP become antigen-presenting cells and stimulate γδ T cells in peripheral blood.…”
mentioning
confidence: 99%
“…Indeed, monocytes treated with ZA and IL-2 displayed an increased phosphorylation of p38 compared to monocytes treated with either IL-2 or ZA alone (data not shown). Moreover, SOCS3 inhibition by ZA [23,24] resulting in enhanced STAT1/3 signaling may contribute to increased IFN-γ production when IL-2 was added to cultures.…”
mentioning
confidence: 99%